Clinical characteristics and prognosis of sudden sensorineural hearing loss in single-sided deafness patients - Liu, Yupeng; Wu, Wenjin; Li, Shuna; Zhang, Qing; He, Jingchun; Duan, Maoli; Yang, Jun (Frontiers in Neurology, 2023)
Background: Sudden sensorineural hearing loss (SSNHL) in patients with single sided deafness (SSD) is rare. Prognosis of the sole serviceable hearing ear is very important for these patients. However, the clinical characteristics and prognosis of SSNHL in SSD patients is not well-documented. Objective: This study aims to investigate the clinical features and treatment outcomes of SSNHL in SSD patients. Methods: Clinical data of 36 SSD patients and 116 non-SSD patients with unilateral SSNHL from January 2013 to December 2022 were retrospectively investigated. Clinical characteristics of the SSD patients were analyzed. All SSD patients were treated with intratympanic steroid plus intravenous steroid. Pure tone average (PTA) and word recognition score (WRS) before and after treatment were recorded. Hearing recovery of SSNHL in SSD patients in comparison with non-SSD patients was explored. Auditory outcomes in SSD patients with different etiology were also compared. Results: Initial hearing threshold showed no significant differences between the SSD group and the non-SSD group (66.41±24.64 dB HL vs 69.21±31.48 dB HL, p=0.625). SSD group had higher post-treatment hearing threshold (median (interquartile range, IQR) 53.13(36.56) dB HL) than non-SSD group (median 32.50(47.5) dB HL, p<0.01). Hearing gains (median 8.75(13.00) dB) and the rate of significant recovery (13.89%) were lower in the SSD group than in the non-SSD group (median 23.75(34.69) dB, 45.69%).The etiology of SSD was classified as SSNHL, special types of infection, chronic otitis media, and unknown causes. SSNHL accounted for the maximal proportion (38.9%) of causes of SSD in SSD group. Hearing gains were lower in SSNHL-SSD group than in other causes of SSD group. Binary logistic regression analysis demonstrated that SSD serves as an indicator of unfavorable hearing recovery outcomes (OR=5.264, p<0.01). Conclusion: The prognosis of SSNHL in SSD patients is unsatisfactory. SSNHL accounts for the maximal proportion of causes of SSD in this group of patients. For SSD patients caused by SSNHL, less hearing improvement after treatment was expected when SSNHL occurred in the contralateral ear in comparison with the SSD patients with other causes.